Analysis of Scientific Literacy and Cultural Civic Literacy in Ethnochemistry-Based Atomic Learning - Leni Nurhafidah; Aulia Salma Sola; Lilis Fatmasari; Restika Wahyuni; Siti Salwa Salsabila; Alya Latifa; Resa Salma Salsabila Az-Zahra; Ghefira Alya Mukhbita; Afridha Laily Alindra (MO.RI Publishing, 2026)
Formal chemistry learning frequently encounters obstacles in the form of student misconceptions and a disconnect between abstract concepts and everyday life, contributing to Indonesia's low scientific literacy scores in PISA 2022. This study examines the reconstruction of ethnochemistry as an integrative learning approach for atomic concepts and analyses its contribution to facilitating scientific literacy while revitalising students' cultural and civic literacy. Employing a descriptive qualitative narrative literature review, data were gathered from credible scientific articles published between 2020 and 2025. The findings indicate that ethnochemistry effectively reconstructs abstract atomic structure concepts into concrete understanding by integrating local wisdom contexts such as batik-making and traditional fermentation. This approach enhances conceptual understanding, minimises misconceptions, and sharpens science process skills. Furthermore, ethnochemistry-based atomic learning strengthens cultural and civic literacy through the internalisation of character values including mutual cooperation, patriotism, and multicultural awareness and supports the formation of the Pancasila Student Profile. Optimising this approach requires innovation in digital media such as e-flipbooks and Augmented Reality, alongside reinforced implementation of the Merdeka Curriculum. These findings underscore the importance of uniting cognitive and affective dimensions within a cultural framework to nurture a generation that is scientifically literate and strong in national character.